Between the riverbed and the banks: multiple water flows, single identity - a dialogue between Guimarães Rosa and Mia Couto - Ribas, Maria Cristina (Status Quaestionis, 2014)
This study is set in-between the torrent and the swamp of senses in different places. To this end, we propose a comparative reading of two short stories: A terceira margem do rio, by Guimarães Rosa (Primeiras Estórias, 1962), written shortly after the construction of the new capital, Brasília, and Nas águas do tempo, by Mia Couto (Estórias Abensonhadas, 1994), shortly following the end of the Mozambique civil war. The Brazilian short story analysis – about a son and his life-long wait on the riverbank for his absent father who doesn’t return and his guilty feeling for betraying the role model and not filling the father’s empty place is compared with the Mozambican tale. Here, an old present grandfather decides to take his grandson sailing into “forbidden territory”, which dramatizes, in fictitious waters, the innovative methodology of Comparative Literature. Free from the paradigm of continuity and subservience to the standard model, no longer tracking sources or dependence on previous understandings or debt, it becomes rewritten (Carvalhal 1986). Our interpretation intends to review debts owed, which implies questioning the concept of the model’s superiority (Silviano 1979) and its counter-face: the submissiveness to the model – here the father and tradition - by converting the new text-son and grandson into another point of reference, liquefied and in which marginalized subjects and descendants meet, regardless of their own impotence and/or ban and yet still constitute a privileged observatory. While the Mozambican tale unfolds, in the comfort of the grandfather´s presence, there is the possibility update a tradition based on community values, the Brazilian short story dramatizes the split between subject and language and the breaking of the knowledge transmission circuit. In rivers that look like the sea, between the river bed and its banks, life and death, reason and myth, there, in that insulated space, plural of waters, you can emancipate yourself: sail in a canoe-cradle/coffin-and create unique identities in plural contexts.